Growth Performance of Potato in India vis-à-vis North East India - Pynbianglang Kharumnuid,; L. Devarani,; Ram Singh, (Indian Journal of Extension Education, 2022)
There is a huge potato yield gap between India and developed countries and between regions within the country. This study examines the trends in potato area, yield, and production in India and North East India from 2000-01 to 2019-20, as well as the causes of the yield gap and the role of improved varieties in bridging it. Over two decades, all parameters showed positive trends in India and North East India, but growth rates were higher at the national level than in North East India. The growth in production was mainly attributed to an increase in area. During TE 2019-20, India produced 50.18 million tons (23.5 t/ha) of potatoes from 2.14 million ha, while North East India produced only 2.78 per cent (10 t/ha) from 8.15 per cent of national potato area. Low potato yield in the region is mainly caused by the lack of knowledge about and low adoption of quality seeds and recent varieties and other scientific potato technologies. State governments, research institutes, private seed companies, public policy bodies, and other potato stakeholders should facilitate the diffusion and adoption of improved varieties and other improved potato technologies to boost potato yield and farmers’ income.